Genital Mycoplasma, Shigellosis, Zika, Pubic Lice, and Other Sexually Transmitted Infections: Neither Gone Nor Forgotten. Issue 4 (April 2021) - Torrone, Elizabeth A.; Lewis, Felicia M. T.; Kirkcaldy, Robert D.; Bernstein, Kyle T.; Ryerson, A. Blythe; de Voux, Alex; Oliver, Sara E.; Quilter, Laura A. S.; Weinstock, Hillard S.
Abstract : Abstract: Most estimates of the combined burden and cost of sexually transmitted infections (STIs) in the United States have focused on 8 common STIs with established national surveillance strategies (chlamydia, gonorrhea, syphilis, trichomoniasis, genital herpes, human papillomavirus, and sexually transmitted human immunodeficiency virus and hepatitis B). However, over 30 STIs are primarily sexually transmitted or sexually transmissible. In this article, we review what is known about the burden of "other STIs" in the United States, including those where sexual transmission is not the primary transmission route of infection. Although the combined burden of these other STIs may be substantial, accurately estimating their burden due to sexual transmission is difficult due to diagnostic and surveillance challenges. Developing better estimates will require innovative strategies, such as leveraging existing surveillance systems, partnering with public health and academic researchers outside of the STI field, and developing methodology to estimate the frequency of sexual transmission, particularly for new and emerging STIs. Abstract : We review the burden of sexually transmitted infections that are not usually included in estimates of the burden of sexually transmitted infections in the United States.Supplemental digital content is available in the text.